PENGEMBANGAN MODUL PEMBELAJARAN TEMATIK INTEGRATIF BERKARAKTER NASIONALISME KELAS IV SEKOLAH DASAR DAERAH BANYUMAS - Tegar Pambudhi; Trie Hartiti Retnowati (Jurnal Pendidikan Karakter, 2017)
Abstrak: Penelitian ini bertujuan menghasilkan modul pembelajaran tematik integratif berkarakter nasionalisme subtema “Aku Bangga dengan Daerah Tempat Tinggalku” yang layak dan efektif untuk meningkatkan aktivitas dan prestasi belajar peserta didik kelas IV SDN 2 Tinggarjaya Banyumas. Desain penelitian mengacu pada RD Borg Gall. Teknik analisis data menggunakan uji t dengan taraf signifikansi 0,05. Kelayakan dari aspek materi skor 147, aspek media skor 91, respons guru skor 60, dan respons peserta didik skor 36,13. Keefektifan dilihat dari pengamatan sikap nasionalisme dengan persentase peserta didik yang menunjukan sikap positif pada kelas eksperimen lebih tinggi daripada kontrol. Pengamatan aktivitas peserta didik pada kelas eksperimen yang menunjukan aktivitas dengan kategori “tinggi” presentasenya lebih besar dibanding dengan kontrol. Hasil analisis data prestasi belajar kelas kontrol dan kelas eksperimen 1 menunjukan taraf signifikansi 0,020, serta pada kelas kontrol dan kelas eksperimen 2 menunjukan taraf signifikansi 0,011. Dengan demikian, modul yang dikembangkan layak digunakan pada kelas IV SD. Kata kunci: modul pembelajaran, tematik integratif, nasionalisme DEVELOPING INTEGRATIVE THEMATIC LEARNING MODULE WITH NATIONALIST CHARACTER FOR CLASS IV ELEMENTARY SCHOOL IN BANYUMAS Abstract: This study aims to generate integrative thematic learning modules with nationalist character; sub-theme: "Aku Bangga dengan Daerah Tempat Tinggalku" that is suitable and effective to enhance the activity and learning outcomes of the grade IV students of SD Negeri 2 Tinggarjaya, Banyumas. This development research refers to the stages developed by Borg Gall. Data analysis technique used t test with significance level of 0.05. The results show that the eligibility from the material aspect that is 147 score, media aspect gets 91 score, the responsse of teachers get 60 score, and the responsse of students get 36.13. The effectiveness can be seen from the observation of nationalism learners who show a positive attitude in the experimental class which has a higher percentage than the control. Furthermore, based on the observation of the activity of learners with the result of the experimental class has a tendency to have activity in the category of "high" percentage which is greater than the control. Then, from the results of the data analysis of learning outcomes in the control class and experimental class 1, indicates a significance level of 0.020, as well as the control class and experimental class 2 shows the significance level of 0.011. It can be concluded that the module developed is feasible use for the grade IV SD. Keywords: learning module, integrative thematic, nationalism